Дівочі образи народних пісень про кохання - Чуй, Андрій; Chuy, Andrii (Східноєвропейський національний університет імені Лесі Українки, 2015)
На матеріалі вибраних пісень про кохання відтворено народнопоетичний портрет закоханої жінки; розкрито символіку асоціативних образів-утілень ліричної героїні; виявлено етнопсихологічні домінанти характеру дівчини; визначено найхарактерніші для народнопісенної практики засоби творення художнього образу; з’ясовано специфіку творення образу ліричної героїні в провідних мотивах народних пісень про кохання. On the material of the chosen folk songs about love the article reproduces the national artistic image of the maiden in love. A research underlines the main accents of a girl’s portrait, which represents national ideal of female beauty. The article reveals the leading motives of folkloric love songs. The paper expounds symbolic meaning of a number of associative images, in which a girl appears to a loving man (symbolic-metaphorical images of a red guelder-rose, heart and a bird (a dove, a turtle-dove)). The investigation finds out some ethnopsychological dominants of the girl’s character, in particular her heightened emotionality and philosophy of cordocentrism. The research shows typical ways of creation of artistic images in folkloric love songs (metaphorization and comparison) and also defines specific way of depiction of an image of the lyrical heroine (using of folklore symbols to depict her outer and inner beauty).
Maiden Images of Folk Songs About Love
Keywords: народні пісні про кохання; дівочі пісні; портрет; образ-символ; метафора; кордоцентризм; folk love songs; maiden songs; portrait; symbol; metaphor; cordocentrism